THE ETHICAL ESSENCE OF THE ANTI-CORRUPTION MENTALITY - Toshpolatova Shirin Muhiddinovna (Journal of Artificial Intelligence and Digital Economy, 2024)
The ethics of domestic civil servants is determined by the Law of the Republic of Uzbekistan “On State Civil Service”, which very succinctly expresses the relevant professional ethics. In our opinion, the section needs an expansive interpretation. Directly in addition to the Law of the Republic of Uzbekistan “On State Civil Service,” the professional ethics of civil servants is also determined by anti-corruption legislative acts and the National Personnel Training Program.